A phase 2 study of a combined diphtheria-tetanus-acellular pertussis vaccine with a Sabin-derived inactivated poliovirus vaccine in children - Takashi Nakano; Shuji Sumino; Yohei Takanami; Nodoka Mitsuya; Keisuke Nakatome (Taylor & Francis Group, 2018)
Background: With the goal of global eradication of poliomyelitis due to wild-type viruses within sight, WHO now recommends that infants receive at least one dose of trivalent inactivated poliovirus vaccine (IPV) with bivalent OPV (types 1 and 3) replacing trivalent OPV. Limited manufacturing capacity and new regulations on manufacturers' use of wild-type viruses is driving the development of IPV based on attenuated Sabin type polioviruses. Takeda are developing a Sabin-based IPV (sIPV) to augment global capacity and supply. Methods: This study was performed to evaluate three dosages (low, medium and high) of the sIPV when administered as a combination vaccine with diphtheria-tetanus-acellular pertussis antigens (DTaP-sIPV) as a three dose primary series or as booster dose in Japanese infants and toddlers. Results: All formulations were immunogenic and well-tolerated with no safety concerns in either infants or toddlers. There was a dosage-dependent induction of neutralizing antibodies against Sabin polioviruses, the only statistically significant differences being between the low-dose and medium- and high-dose sIPVs. There was good correlation of neutralizing antibodies against Sabin and wild-type polioviruses. No sIPV dose had an observable effect on immune responses to DTaP components or the reactogenicity profile of the combined vaccine. Conclusion: When administered as a DTaP-sIPV combination, Takeda's sIPV vaccine was well-tolerated and highly immunogenic in infant and toddler schedules. The medium-dose formulation offers the optimal balance between immunogenicity and potential dose-sparing to provide a new source of sIPV to enhance the global supply, while mitigating the environmental risks associated with manufacturing vaccines with wild-type viruses.